Metacognitive Reading Strategies and Their Impact on Comprehension: Insights from Rural EFL Learners - Novri Pahrizal; Aridem Vintoni; Rimajon Sotlikova; Hajah Zurinah Haji Ya'akub (Universitas Muhammadiyah Surakarta, 2025)
The need for more understanding and implementation regarding the importance of metacognitive reading strategies has constrained reading skills learning among EFL learners. While these strategies improve reading comprehension, learners must still utilize them effectively, reducing their performance in reading texts critically and independently. This study examines the influence of metacognitive awareness reading strategies on reading comprehension among rural EFL learners. This study exploited cross-sectional design, one of two major designs of survey methods. This study employed 114 EFL learners of the English Department in Indonesia. This study employed two instruments, namely a questionnaire to measure EFL learners’ metacognitive awareness reading strategies from MARSI-R by Mokhtari et al. (2018) and documentation obtained from the scores of the reading courses in the third semester. This study used quantitative statistical analysis, descriptive statistics to analyze the ability level of EFL learners to read comprehension, and inferential statistics to determine the influence of metacognitive awareness reading strategies on reading comprehension among EFL learners. The result of this study revealed that reading comprehension among EFL learners is at a moderate level. EFL learners are highly aware of metacognitive reading strategies, especially problem-solving strategies. These subscales also strongly correlate with each other and metacognitive awareness reading strategies for improving readers’ metacognitive ability to understand texts. Then, metacognitive reading strategies have a significant relationship but a weak impact on reading comprehension, explaining only slight variability. Regularly employing metacognitive strategies can improve reading performance and effectiveness, making learners more strategic and skilled in planning, monitoring, and evaluating their reading comprehension.